High-precision 3D real scene model construction method based on air-ground data combination. Issue 4 (October 2020) - Yang, Fei; Ma, Chengrong; Zhang, Bowen; Chen, Xuannan; Cao, Li; Li, Changhong; Huang, Yongliang
Abstract: Due to low efficiency, low accuracy, and difficulty in intuitively realizing the real geological conditions for spatial data acquisition on mines and slopes, this study proposes the use of a 3D modeling method based on a combination of air and ground data. The method is based on Unmanned Air View (UAV) tilt photogrammetry data. In this article, 3D terrestrial laser scanning point cloud data is used as a supporting technique via control points to spatially fuse and improve the accuracy of the UAV tilt photogrammetry 3D model. This study uses the feature points to adjust the interior point coordinates of the UAV tilt photogrammetry 3D model. The application results show that the mining site model established by this method has high precision and processing efficiency. It can also display the overall characteristics of mines and provide a scientific basis for mining, exploration, measurement, and effective evaluation of slope stability.